Development of Rainfall Erosivity (R) In Revised Universal Soil Loss Equation (RUSLE) For An Equatorial Region Of Sarawak - Johari, A.H.; Law, P.L.; Taib, S.N.L.; Darrien, M.Y.S.; Yong, L.K. (IJES, 2018)
The Revised Universal Soil Loss Equation (RUSLE) was developed for the Department of Agriculture of USA for predicting top soil erosion rate and sediment yield from agricultural areas or plantations located in temperate region, with extremely low annual rainfall (1,000 mm/year), as compared to equatorial region of more than 4,000 mm/year such as Sarawak whereby a great portion (>25%) of land area covered with peat. The primary objective of this research was to develop the factors of Rainfall Erosivity (R) for an equatorial region of Sarawak. In order to achieve the objective of this study, soil samples were collected from Sri Aman, Sarawak. The soil samples were tested for physical properties. A rainfall simulator was constructed to conduct six simulated rainfalls on three types of hill slopes; a cone, a pyramid, and a plateau. Photos of raindrops were taken with a high speed camera during simulated rainfalls to determine raindrop sizesand consequently to determine kinetic energy of the raindrops. Runoff samples were taken to determine sediment concentration. From the experimental results, it was observed that the median drop diameter for simulated rainfalls on the plateau-shape hill slope and cone-shaped hill slope was 2.0 mm. For simulated rainfall on pyramid-shaped hill slope, the median drop diameter was 2.5 mm. Values of total kinetic energy of raindrops on plateau-shaped hill slope, cone-shaped hill slope, and pyramid-shaped hill slope were 0.287 MJ/ha.mm, 0.332 MJ/ha.mm and 0.317 MJ/ha.mm, respectively. The rainfall intensities for simulated rainfalls on plateau-shaped hill slope, coneshaped hill slope and pyramid-shaped hill slope were 142.96 mm/h, 142.78 mm/h, and 151.17 mm/h, respectively. An equation of Total Kinetic Energy of rainfall for an equatorial region of Sarawak (Eeqt) was derived from correlations of kinetic energy of rainfall and rainfall intensity. The values of Equatorial Rainfall Erosvity (ER) were determined from multiplication of 30-minute rainfall intensity and Equatorial Kinetic Energy of Rainfall (Eeqt). Results of Equatorial Rainfall Erosivity (ER) and Rainfall Erosivity (R) were compared for the rainfall station of Kuching in the year 2014.